The Effects of Adverse Childhood Experiences ( ACEs ) on Change in Emotion Regulation Difficulty in Clinical Couples - Betsy Hughes Barrow; Angela B. Bradford; Justin W. Dyer; Alyssa Banford Witting; Lee N. Johnson (Family Process, 2026)
ABSTRACT Emotion regulation is central to managing emotions and interactions, making it essential for effective relationship functioning. Because emotion dysregulation contributes to many presenting problems in couple therapy, understanding it within clinical couples is vital, particularly when one or both partners have a history of adverse childhood experiences (ACEs). While the link between ACEs and adult mental and relational challenges is well‐established, research about how ACEs affect the therapy change process is still developing. Most existing research about ACEs has focused on cumulative ACE counts, with less attention to exposure to distinct ACE types (within the family context) and their differential effects on emotion regulation. The current study focuses on emotion regulation difficulty in clinical couples, exploring associations with frequency of exposure to individual ACE types—such as abuse, neglect, and various types of family of origin dysfunction—and levels of emotion regulation difficulty at intake as well as the trajectory of emotion regulation difficulty over 12 sessions of couple therapy. Findings were that emotional maltreatment (abuse and neglect) and mental illness in one's family of origin were associated with higher levels of emotion regulation difficulty at intake. Also, greater frequency of emotional neglect in childhood was associated with faster rates of change in emotion regulation difficulty over 12 therapy sessions. Findings suggest that assessing the frequency of family‐of‐origin adversity may be clinically relevant in couple therapy contexts and that individuals with histories of neglect may experience improvement in emotion regulation within supportive relational environments characteristic of couple therapy.